2013
DOI: 10.5551/jat.14035
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylated-Oxidized LDL: Proatherosclerotic Effects on Endothelial Cells and Macrophages

Abstract: Aim Both oxidized LDL and carbamylated LDL are considered important for initiating atherosclerosis in patients with end-stage kidney disease through vascular endothelial cell dysfunction or injury. However their effects on each other and their relationship related to pro-atherosclerotic effects on endothelial cells and macrophages have not been investigated. In this study, we analyzed the competition between LDL carbamylation and oxidation, tested biological effects of carbamylated-oxidized LDL (coxLDL) toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
(69 reference statements)
0
27
0
1
Order By: Relevance
“…Carbamylated low-density lipoprotein has also been shown to markedly accelerate atherosclerosis and to reduce myocardial function in mice. 80 Levels of carbamylated proteins provide a time-averaged indicator of urea concentration (analogous to the widespread use of hemoglobin A 1c to indicate glycemic control in individuals with diabetes mellitus). Berg et al 78 and Drechsler et al 81 reported that higher levels of carbamylated albumin (C-Alb) are associated with a higher risk of all-cause mortality and uremic heart failure in both incident and prevalent ESRD populations.…”
Section: Protein Carbamylationmentioning
confidence: 99%
“…Carbamylated low-density lipoprotein has also been shown to markedly accelerate atherosclerosis and to reduce myocardial function in mice. 80 Levels of carbamylated proteins provide a time-averaged indicator of urea concentration (analogous to the widespread use of hemoglobin A 1c to indicate glycemic control in individuals with diabetes mellitus). Berg et al 78 and Drechsler et al 81 reported that higher levels of carbamylated albumin (C-Alb) are associated with a higher risk of all-cause mortality and uremic heart failure in both incident and prevalent ESRD populations.…”
Section: Protein Carbamylationmentioning
confidence: 99%
“…Thirdly, MPO catalyzed the addition of thiocyanate to the LDL (derived from the decomposition of urea) and leads to the formation of carbamylated-LDL (cLDL) [66,67]. These cLDL have potent pro-atherogenic effects such as the transformation of macrophages into foam cells [68] through their binding to the pro-atherogenic CD36 receptor [69] (upregulated in CKD [70]) and associated with endothelial toxicity [71,72] and platelet aggregation [73] through LOX-1 [74]. cLDL levels are raised by chronic uremia and were linked with atherosclerosis in CKD [75,76].…”
Section: Uremic Lipoproteins Evidences Of Toxicitymentioning
confidence: 99%
“…Protein carbamylation is associated with cardiovascular disease [186], mortality in CKD [187,188] and can also affect lipoproteins [75] and promote atherosclerotic complications [68,189] (Figure 3). …”
Section: Oxidative Stress/non-oxidative Modifications Of Lipids Anmentioning
confidence: 99%
“…In addition, the presence of AGES and glycosylated LDL in the lesion will be detected by RAGE expressed on macrophages and promote inflammation. Thus, the presence of other forms of modified LDL inside atheromas will be enough to justify a dangerous and accelerated evolution of atheromas in people with diabetes, smokers and patients with chronic kidney disease [99,127,128]. Several canonical ligands of TLRs can potentially be present in the lesions and mediate the polarisation of macrophages towards M1 functions.…”
Section: How Risk Factors and Comorbidities Could Cooperate With Ox-lmentioning
confidence: 99%
“…In uremic patients and smokers these other forms of modified LDL seem to be much more dangerous than ox-LDL. It has been demonstrated that LDL can be simultaneously carbamylated and oxidised making them highly cytotoxic to endothelial cells [99].…”
Section: Ox-ldl In Cooperation With Risk Factors Becomes An Injuriousmentioning
confidence: 99%